Preparation method and application of composite polyurea coating with metal concentration gradient
By preparing a composite polyurea coating with a metal concentration gradient on the lithium battery positive electrode material, the problem of difficulty in continuously changing component concentration in the coating in the prior art is solved, and higher stability and cycling performance are achieved.
Patent Information
- Application Number
- CN202411538909.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-14
AI Technical Summary
The existing lithium battery positive electrode material coatings are difficult to achieve continuous changes in the concentration of different components in the coating, resulting in peeling between layers during the electrochemical cycle, affecting stability.
Using the preparation method of a composite polyurea coating with a metal concentration gradient, the molecular layer deposition technology is used to deposit on the positive electrode material in the order of high, medium and low metal concentration layers to form a metal content coating that changes continuously from the inside to the outside.
The continuous changes in component concentration in the coating are achieved, the mechanical properties of the interface layer are enhanced, the matching between the positive electrode material and the electrolyte or solid electrolyte is improved, and the stability and circulation capacity retention rate of the positive electrode material are significantly improved.
Smart Images

Figure CN119608526A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of interface engineering of lithium battery positive electrode materials, and specifically relates to a method for preparing a composite polyurea coating with a metal concentration gradient. The present invention also relates to the application of the composite polyurea coating with a metal concentration gradient. Background Art
[0002] In the development process of lithium battery systems, in order to meet a variety of application scenarios (including electric vehicles, large-scale energy storage, portable electronic devices, etc.), the industry has put forward higher requirements on battery energy density, safety and service life.
[0003] The cathode material is a key part of the four parts of the battery. The current mainstream cathode materials include: lithium iron phosphate, ternary cathode materials, high-voltage lithium-rich cathode, lithium cobalt oxide, etc. Due to their relatively high theoretical capacity, cycle stability has received widespread attention. At present, the development of lithium battery cathodes still faces fundamental challenges, including irreversible phase change, low high-voltage stability, cathode particle cracking, interface instability, etc.
[0004] Among the current methods of modifying cathode materials, applying a coating layer on the cathode surface to improve stability is a common method. Most of the current coatings have the same internal and external composition, and cannot simultaneously match the interface at the cathode and the interface between the solid electrolyte or electrolyte. Even for double-layer or multi-layer coatings, the composition changes between the layers cannot be continuous, which will cause peeling between the layers during the electrochemical cycle. Therefore, it is still a huge challenge to form a coating with continuous changes in the composition of the coating through composition regulation. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a composite polyurea coating with a metal concentration gradient, which solves the problem in the prior art that it is difficult to achieve continuous changes in the concentrations of different components in the positive electrode material coating.
[0006] Another object of the present invention is to provide applications of composite polyurea coatings having a metal concentration gradient.
[0007] The first technical solution adopted by the present invention is a method for preparing a composite polyurea coating having a metal concentration gradient, which is specifically implemented according to the following steps: Step 1, sieve the positive electrode material until the particles are uniform; Step 2, placing the positive electrode material screened in step 1 into a molecular layer deposition chamber for preheating, so that the positive electrode material is preheated to the same temperature as the chamber; Step 3, add the required precursors; and preheat until all precursors reach the target temperature; Step 4: Perform molecular layer deposition on the positive electrode material in the order of high metal concentration layer-medium metal concentration layer-low metal concentration layer, or in the reverse order, i.e., low metal concentration layer-medium metal concentration layer-high metal concentration layer, to obtain a composite polyurea coating with a metal concentration gradient.
[0008] The first technical solution of the present invention is also characterized in that: The positive electrode material in step 1 is one or more of lithium iron phosphate, ternary layered oxide positive electrode, lithium cobalt oxide, and lithium-rich positive electrode; The chamber temperature in step 2 is 20-110° C., an inert gas is used as a carrier gas, the carrier gas flow rate is set to 5-100 sccm, and the chamber is left to stand for 5 minutes.
[0009] The precursors required in step 3 include metal precursors, amine precursors, and isocyanate precursors; The preheating temperature of metal precursor is 15~185℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~30s; the preheating temperature of amine precursor is 15~100℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~30s; the preheating temperature of isocyanate precursor is 15~200℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~35s, and wait for 5 minutes.
[0010] The metal precursor in step 3 is one or more of trimethylaluminum, diethylzinc, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, or pentaethoxytantalum.
[0011] The amine precursor in step 3 is one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.
[0012] The isocyanate precursor in step 3 is one or more of 1,4-butyl diisocyanate and phenylene diisocyanate.
[0013] In step 4, the high metal concentration layer has a cycle period of metal precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle period of molecular layer deposition is set to X, where the range of X is a positive integer of 1-100.
[0014] In step 4, the metal concentration layer has a cycle period of metal precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle period of molecular layer deposition is set to Y, and the range of Y is a positive integer of 1 to 100.
[0015] In step 4, the low metal concentration layer has a cycle of metal precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle number of molecular layer deposition is set to Z, and the range of Z is a positive integer of 1 to 100.
[0016] The second technical solution adopted by the present invention is that the composite polyurea coating with a metal concentration gradient is applied to the interface protection of lithium battery positive electrode materials.
[0017] The beneficial effect of the present invention is that the preparation method of the composite polyurea coating with a metal concentration gradient, the interface protection layer is a coating with a metal content that continuously changes from the inside to the outside obtained by introducing a certain metal inorganic component into the polyurea coating, and the coating can reflect different interface properties from the inside to the outside, and at the same time match the internal positive electrode material and the external liquid electrolyte or solid electrolyte. The coating can accurately control the thickness, metal content, metal concentration gradient and other properties by adjusting the conditions such as the source entry time of the precursor source, the carrier gas flow rate, and the number of repeated cycles. The preparation method of the composite polyurea coating with a metal concentration gradient is convenient and has strong repeatability. This method can improve the mismatch between the positive electrode interface and the electrolyte or solid electrolyte due to different physical and chemical properties, reduce the side reactions existing at the interface, enhance the mechanical properties of the interface layer, and make the positive electrode material show excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The coated LiNi in Example 1 of the present invention 0.5 Mn 0.3 Co 0.2 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells; Figure 2 The coated LiNi obtained in Example 2 of the present invention 0.5 Mn 0.3 Co 0.2 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells; Figure 3 The coated LiNi in Example 3 of the present invention 0.8 Mn 0.1 Co 0.1 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells; Figure 4 The coated LiNi in Example 4 of the present invention 0.8 Mn 0.1 Co0.1 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] The method for preparing the composite polyurea coating having a metal concentration gradient of the present invention is specifically implemented according to the following steps: Step 1: Use a metal sieve to sieve the positive electrode material until the particles are uniform; Step 2, placing the positive electrode material screened in step 1 into a molecular layer deposition chamber for preheating, so that the positive electrode material is preheated to the same temperature as the chamber; Step 3, add the required precursors; and preheat until all precursors reach the target temperature; Step 4: Perform molecular layer deposition on the positive electrode material in the order of high metal concentration layer-medium metal concentration layer-low metal concentration layer, or in the reverse order, i.e., low metal concentration layer-medium metal concentration layer-high metal concentration layer, to obtain a composite polyurea coating with a metal concentration gradient.
[0021] The positive electrode material in step 1 is a common commercial positive electrode material, which is one or more of lithium iron phosphate, ternary layered oxide positive electrode, lithium cobalt oxide, and lithium-rich positive electrode; The chamber temperature in step 2 is 20-110° C., an inert gas is used as a carrier gas, the carrier gas flow rate is set to 5-100 sccm, and the chamber is left to stand for 5 minutes.
[0022] The precursors required in step 3 include metal precursors, amine precursors, and isocyanate precursors; The preheating temperature of metal precursor is 15~185℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~30s; the preheating temperature of amine precursor is 15~100℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~30s; the preheating temperature of isocyanate precursor is 15~200℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~35s, and wait for 5 minutes.
[0023] The metal precursor in step 3 is one or more of trimethylaluminum, diethylzinc, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, or pentaethoxytantalum.
[0024] The amine precursor in step 3 is one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.
[0025] The isocyanate precursor in step 3 is one or more of 1,4-butyl diisocyanate and phenylene diisocyanate.
[0026] In step 4, the high metal concentration layer has a cycle period of metal precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle period of molecular layer deposition is set to X, where the range of X is a positive integer of 1-100.
[0027] In step 4, the metal concentration layer has a cycle period of metal precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle period of molecular layer deposition is set to Y, and the range of Y is a positive integer of 1 to 100.
[0028] In step 4, the low metal concentration layer has a cycle of metal precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle number of molecular layer deposition is set to Z, and the range of Z is a positive integer of 1 to 100.
[0029] Composite polyurea coating with metal concentration gradient is used for interface protection of lithium battery positive electrode materials.
[0030] The raw materials and reagents used in the present invention are commercially available.
[0031] Example 1 This example is a LiNi coated with a polyurea coating containing an aluminum concentration gradient. 0.5 Mn 0.3 Co 0.2 The preparation method of O2 positive electrode is as follows: S1, LiNi 0.5 Mn 0.3 Co 0.2 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 65°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.
[0032] S2, set the preheating temperature of the precursor trimethylaluminum to 25°C, the pulse time to 1s, and the purge time to 20s, set the preheating temperature of the precursor 1,4-butyl diisocyanate to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s. Set the preheating temperature of the precursor ethylenediamine to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s.
[0033] S3, performing molecular layer deposition on the positive electrode particles in the order of low metal concentration layer-medium metal concentration layer-high metal concentration layer. The number of deposition turns for the low metal concentration layer is set to 1 turn, the number of deposition turns for the medium metal concentration layer is set to 2 turns, and the number of deposition turns for the high metal concentration layer is set to 4 turns.
[0034] S4, the coated LiNi prepared above 0.5 Mn 0.3 Co 0.2 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of the positive material is 5 mg / cm 2 .
[0035] S5. Dry the prepared positive electrode sheet in a vacuum oven with the temperature set to 110° C. and assemble the battery using a carbonate electrolyte.
[0036] Electrochemical performance test: The coated LiNi obtained in this example 0.5 Mn 0.3 Co 0.2 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 1 As shown, after 200 cycles at a current of 0.5C, the coated LiNi 0.5 Mn 0.3 Co 0.2 The cycle capacity retention rate of O2 positive electrode material has been significantly improved, with the capacity retention rate reaching 99.6% after 200 charge and discharge cycles, while the capacity retention rate of the uncoated positive electrode after 200 cycles is 96.9%.
[0037] Example 2 This example is a LiNi coated with a polyurea coating containing an aluminum concentration gradient. 0.5 Mn 0.3 Co 0.2 The preparation method of O2 positive electrode is as follows: S1, LiNi0.5 Mn 0.3 Co 0.2 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 65°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.
[0038] S2, set the preheating temperature of the precursor trimethylaluminum to 25°C, the pulse time to 1s, and the purge time to 20s, set the preheating temperature of the precursor 1,4-butyl diisocyanate to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s. Set the preheating temperature of the precursor ethylenediamine to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s.
[0039] S3, performing molecular layer deposition on the positive electrode particles in the order of high metal concentration layer-medium metal concentration layer-low metal concentration layer. The number of deposition turns of the high metal concentration layer is set to 4 turns, the number of deposition turns of the medium metal concentration layer is set to 2 turns, and the number of deposition turns of the low metal concentration layer is set to 1 turn.
[0040] S4, the coated LiNi prepared above 0.5 Mn 0.3 Co 0.2 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of the positive material is 5 mg / cm 2 .
[0041] S5. Dry the prepared electrode in a vacuum oven with the temperature set at 110°C, and assemble the battery using a carbonate electrolyte.
[0042] Electrochemical performance test: The coated LiNi obtained in this example 0.5 Mn 0.3 Co 0.2 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 2 As shown, after 200 cycles at a current of 0.5C, the coated LiNi 0.5 Mn 0.3 Co 0.2 The cycle capacity retention rate of O2 positive electrode material is significantly improved, and the capacity retention rate of 200 charge and discharge cycles is as high as 97.9%. The capacity retention rate of the uncoated positive electrode after 200 cycles is as high as Figure 1 Shown is 96.9%.
[0043] Example 3 This example is a LiNi coated with a polyurea coating containing an aluminum concentration gradient. 0.8 Mn 0.1 Co 0.1 The preparation method of O2 positive electrode is as follows: S1, LiNi 0.8 Mn 0.1 Co 0.1 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 65°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.
[0044] S2, set the preheating temperature of the precursor trimethylaluminum to 25°C, the pulse time to 1s, and the purge time to 20s, set the preheating temperature of the precursor 1,4-butyl diisocyanate to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s. Set the preheating temperature of the precursor ethylenediamine to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s.
[0045] S3, performing molecular layer deposition on the positive electrode particles in the order of low metal concentration layer-medium metal concentration layer-high metal concentration layer. The number of deposition turns for the low metal concentration layer is set to 1 turn, the number of deposition turns for the medium metal concentration layer is set to 2 turns, and the number of deposition turns for the high metal concentration layer is set to 4 turns.
[0046] S4, the coated LiNi prepared above 0.8 Mn 0.1 Co 0.1 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of the positive material is 5 mg / cm 2 .
[0047] S5. Dry the prepared positive electrode sheet in a vacuum oven with the temperature set to 110° C. and assemble the battery using a carbonate electrolyte.
[0048] Electrochemical performance test: The coated LiNi obtained in this example 0.8 Mn 0.1 Co 0.1 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 3 As shown, after 200 cycles at a current of 0.5C, the coated LiNi 0.8 Mn0.1 Co 0.1 The cycle capacity retention rate of O2 positive electrode material has been significantly improved, with the capacity retention rate reaching 93.7% after 200 charge and discharge cycles, and the capacity retention rate of the uncoated positive electrode being 87.3%.
[0049] Example 4 This example is a LiNi coated with a polyurea coating containing an aluminum concentration gradient. 0.8 Mn 0.1 Co 0.1 The preparation method of O2 positive electrode is as follows: S1, LiNi 0.8 Mn 0.1 Co 0.1 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 65°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.
[0050] S2, set the preheating temperature of the precursor trimethylaluminum to 25°C, the pulse time to 1s, and the purge time to 20s, set the preheating temperature of the precursor 1,4-butyl diisocyanate to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s. Set the preheating temperature of the precursor ethylenediamine to 90°C, the pulse time to 1s, the purge time to 20s, and the preheating temperature of the precursor water to 20°C, the pulse time to 1s, and the purge time to 22s.
[0051] S3, performing molecular layer deposition on the positive electrode particles in the order of high metal concentration layer-medium metal concentration layer-low metal concentration layer. The number of deposition turns of the high metal concentration layer is set to 4 turns, the number of deposition turns of the medium metal concentration layer is set to 2 turns, and the number of deposition turns of the low metal concentration layer is set to 1 turn.
[0052] S4, the coated LiNi prepared above 0.8 Mn 0.1 Co 0.1 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of the positive material is 5 mg / cm 2 .
[0053] S5. Dry the prepared positive electrode sheet in a vacuum oven with the temperature set to 110° C. and assemble the battery using a carbonate electrolyte.
[0054] Electrochemical performance test: The coated LiNi obtained in this example 0.8 Mn 0.1 Co 0.1The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 4 As shown, after 200 cycles at a current of 0.5C, the coated LiNi 0.8 Mn 0.1 Co 0.1 The cycle capacity retention rate of O2 positive electrode material is significantly improved, and the capacity retention rate after 100 charge and discharge cycles is as high as 92.6%. Figure 3 Shown is 87.3%.
Claims
1. A method for preparing a composite polyurea coating having a metal concentration gradient, characterized in that: Follow the steps below to implement it: Step 1, sieve the positive electrode material until the particles are uniform; Step 2, placing the positive electrode material screened in step 1 into a molecular layer deposition chamber for preheating, so that the positive electrode material is preheated to the same temperature as the chamber; Step 3, add the required precursors; and preheat until all precursors reach the target temperature; Step 4: Perform molecular layer deposition on the positive electrode material in the order of high metal concentration layer-medium metal concentration layer-low metal concentration layer, or in the reverse order, i.e., low metal concentration layer-medium metal concentration layer-high metal concentration layer, to obtain a composite polyurea coating with a metal concentration gradient.
2. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: The positive electrode material in step 1 is one or more of lithium iron phosphate, ternary layered oxide positive electrode, lithium cobalt oxide, and lithium-rich positive electrode; The chamber temperature in step 2 is 20-110° C., an inert gas is used as a carrier gas, the carrier gas flow rate is set to 5-100 sccm, and the chamber is left to stand for 5 minutes.
3. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: The precursors required in step 3 include metal precursors, amine precursors, and isocyanate precursors; The preheating temperature of metal precursor is 15~185℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~30s; the preheating temperature of amine precursor is 15~100℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~30s; the preheating temperature of isocyanate precursor is 15~200℃, the pulse time is set to 0.1~2s, and the purge time is set to 10~35s, and wait for 5 minutes.
4. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: The metal precursor in step 3 is one or more of trimethylaluminum, diethylzinc, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, or pentaethoxytantalum.
5. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: The amine precursor in step 3 is one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.
6. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: The isocyanate precursor in step 3 is one or more of 1,4-butyl diisocyanate and phenylene diisocyanate.
7. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: In the step 4, the high metal concentration layer has a cycle period of metal precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle period of molecular layer deposition is set to X, where X is a positive integer ranging from 1 to 100.
8. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: In the step 4, the metal concentration layer has a cycle period of metal precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle period of molecular layer deposition is set to Y, and the range of Y is a positive integer of 1 to 100.
9. The method for preparing a composite polyurea coating having a metal concentration gradient according to claim 1, characterized in that: In the step 4, the low metal concentration layer has a cycle of metal precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor-isocyanate precursor-amine precursor, and the cycle number of molecular layer deposition is set to Z, and the range of Z is a positive integer of 1 to 100.
10. A composite polyurea coating having a metal concentration gradient, characterized in that: Applied to the interface protection of lithium battery positive electrode materials.